1992
DOI: 10.1111/j.1439-0507.1992.tb00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal yeast flora of pregnant women in the Gusco region of Peru

Abstract: Summary. A study of the vaginal yeast flora in pregnant women living in Cusco and in its region (Peru), located approximately 3000 m above sea level, is reported. We observed 300 pregnant, healthy and non‐diabetic women who attended a gynaecological clinic in the Lorena, Regional or IPSS (Institute Peruano de Seguridad Social) hospitals in Cusco. A comprehensive clinical history was obtained from each patient. It included age, work, parity, time of pregnancy, use of contraceptives or antibiotics, type of vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Depending on the age, locality, and social economical status, the frequency of vaginal yeast isolates has been reported to be between 5% and 48.4% in healthy nonpregnant women [ 4 – 6 ]. During pregnancy, an increase of 7.8% and 67.8% of yeast vaginal isolates has been reported [ 7 , 8 ]. A study in Jordan revealed a different distribution of strains of Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the age, locality, and social economical status, the frequency of vaginal yeast isolates has been reported to be between 5% and 48.4% in healthy nonpregnant women [ 4 – 6 ]. During pregnancy, an increase of 7.8% and 67.8% of yeast vaginal isolates has been reported [ 7 , 8 ]. A study in Jordan revealed a different distribution of strains of Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we obtained isolates of C. albicans, Rhodotorula spp., C. parapsilosis, N. glabratus, C. tropicalis, and Saccharomyces cerevisiae. All these species have already been reported several times in samples from the female genital region, particularly from the vagina [9,11,12,[17][18][19][20][21][22]25]. We analyzed the samples from patients with symptoms of vaginal, vulvovaginal, or vulvar infections, as well as from patients with uncharacteristic or mild symptoms and asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note as well that several species of rare yeasts are medically important in Latin America, even though cases of severe infections have not been reported in many countries. S. cerevisiae, Rhodotorula sp., and T. cutaneum were found as part of the vaginal yeast flora, some of them causing vulvovaginitis, in pregnant women living in Peru [128]. Trichosporon and Rhodotorula species have been reported as causing vaginosis in Venezuela [129].…”
Section: Discussionmentioning
confidence: 99%